2019
DOI: 10.1021/acs.orglett.9b03542
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Selective Iron Catalysis for α-Amino C–H Bond Functionalization via Aerobic Oxidation

Abstract: Single-electron oxidation and α-deprotonation of tertiary anilines using Fe­(phen)3(PF6)3 afford α-aminoalkyl radicals, which can be coupled with electrophilic partners to afford various tetrahydroquinolines. Mechanistically, the Fe­(phen) n 2+/3+ catalytic cycle is maintained by O2 or a TBHP oxidant, and the presence of the oxygen bound iron complex, Fe­(III)–OO­(H), was elucidated by electron paramagnetic resonance and electrospray ionization mass spectrometry. This redox-selective nonheme iron catalyst beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 65 publications
4
47
0
Order By: Relevance
“…[Fe(tpy) 2 ][PF 6 ] 3 is reported [17] to have been synthesized according to a general procedure [18] . In our hands, we have found a recently reported route to Fe 3+ pyridyl compounds with PbO 2 as an oxidant to arrive at the desired [Fe(tpy) 2 ][PF 6 ] 3 complex [19] . Briefly, [Fe(tpy) 2 ][PF 6 ] 3 begins with complexation of Fe(SO 4 ) ⋅ 7H 2 O in H 2 O with 2 equivalents of 2,2′;6′,2“‐terpyridine followed by addition of 1 M H 2 SO 4 and excess PbO 2 .…”
Section: Resultsmentioning
confidence: 93%
“…[Fe(tpy) 2 ][PF 6 ] 3 is reported [17] to have been synthesized according to a general procedure [18] . In our hands, we have found a recently reported route to Fe 3+ pyridyl compounds with PbO 2 as an oxidant to arrive at the desired [Fe(tpy) 2 ][PF 6 ] 3 complex [19] . Briefly, [Fe(tpy) 2 ][PF 6 ] 3 begins with complexation of Fe(SO 4 ) ⋅ 7H 2 O in H 2 O with 2 equivalents of 2,2′;6′,2“‐terpyridine followed by addition of 1 M H 2 SO 4 and excess PbO 2 .…”
Section: Resultsmentioning
confidence: 93%
“…The past decade, various methods for the synthesis of tetrahydro‐pyrrolo[3,4‐c]quinolinones, which via aromatization can lead to the desired pyrrolo[3,4‐c]quinolinones, [7d,e] have been developed, primarily focusing on the oxidative annulation by utilizing a catalyst and either air or oxygen or a chemical reagent as the oxidant. Various examples exist in literature employing mainly metal catalysts [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Various examples exist in literature employing mainly metal catalysts [7] . For example, Kang and coworkers showed that the reaction can be performed with the use of an iron (III) complex and as the external oxidant, which is essential for the completion of the transformation, they used either TBHP or air (Scheme 1A) [7e] . Similarly, Gogoi and coworkers used CeO 2 as the catalyst and air as the oxidant, in order to perform this oxidative annulation (Scheme 1B) [7d] .…”
Section: Introductionmentioning
confidence: 99%
“…The reaction of acyclic α,β‐unsaturated compounds with N , N ‐dialkylanilines has the possibility of enabling the synthesis of 1,2,3,4‐THQs possessing a wide variety of substituents with control of trans / cis diastereo‐ and enantioselectivity. However, there are very few reports on photo‐ and non‐photoinduced reactions with acyclic α,β‐unsaturated compounds, for example, arylidene malononitrile, [5a, 21] dialkyl fumarate, [5b, 7d, 20d] and 1‐(2‐alkenoyl)‐3,5‐dimethylpyrazole [22] . Among the three types of acyclic α,β‐unsaturated compounds, 1‐(2‐alkenoyl)‐3,5‐dimethylpyrazole has been utilized for the reaction of N , N ‐dialkylaniline to give 1,2,3,4‐THQs in which a bidentate chelation complex of a chiral Lewis acid, ( R , R )‐DBFOX/Ph ⋅ Ni II (( R , R )‐DBFOX/Ph=( R , R )‐4,6‐dibenzofurandiyl‐2,2′‐bis(4‐phenyloxazoline)), [23] with 1‐(2‐alkenoyl)‐3,5‐dimethylpyrazole serves as a photocatalyst; [22] however, only two reactions have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%